Prescription drug monitoring program utilization in Kentucky community pharmacies - Wixson SE; Blumenschein K; Goodin AJ; Talbert J; Freeman PR (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Objective: Identify characteristics of Kentucky community pharmacists and community pharmacists' practice environment associated with utilization of the Kentucky All Schedule Prescription Electronic Reporting Program (KASPER). Methods: Surveys were mailed to all 1,018 Kentucky pharmacists with a KASPER account and an additional 1,000 licensed pharmacists without an account. Bivariate analyses examined the association between KASPER utilization and practice type (independent or chain) and practice location (rural or urban). A multivariate Poisson regression model with robust error variance estimated risk ratios (RR) of KASPER utilization by characteristics of pharmacists' practice environment. Results: Responses were received from 563 pharmacists (response rate 27.9%). Of these, 402 responses from community pharmacists were included in the analyses. A majority of responding pharmacists (84%) indicated they or someone in their pharmacy had requested a patient's controlled substance history since KASPER's inception. Bivariate results showed that pharmacists who practiced in independent pharmacies reported greater KASPER utilization (94%) than pharmacists in chain pharmacies (75%; p<0.001). Multivariate regression results found utilization of KASPER varied significantly among practice environments of community pharmacists with those who practiced in an urban location (RR: 1.11; [1.01-1.21]) or at an independent pharmacy (RR: 1.27; [1.14-1.40]) having an increased likelihood of KASPER utilization. Conclusion: Utilization of KASPER differs by community pharmacists' practice environment, predominantly by practice type and location. Understanding characteristics of community pharmacists and community pharmacists' practice environment associated with PDMP use is necessary to remove barriers to access and increase utilization thereby increasing PDMP effectiveness.